The Daily Menu in Times of Pandemic for Individuals with Anxiety and Depression - Daniela Gomes Alcoforado; Miriam Leite Farias; Juliana Gonçalves Machado; Francisco Vicente Sales Melo; Thomas Kühn (SER Social)
The COVID-19 pandemic brought to light food and nutrition vulnerabilities in society, which were aggravated by the effects of social isolation and other measures to contain coronavirus spread in people’s lives. This study explores how individuals with mental disorders are reacting to this pandemic time, focusing in the context of their eating habits. For that, nineteen in-depth interviews were conducted with people previously diagnosed with depression and/or anxiety. We found out that the pandemic affected food and nutrition security for the participants, once it has acted as a trigger activating vulnerabilities that make this part of society more susceptible to negative changes in eating habits. They are consuming unhealthy food, and experiencing emotional eating and weight change. Also, financial problems, unemployment, and the rise of food prices were worsened by the pandemic, causing food access difficulties for few participants. Suggestions for policymakers were highlighted on the conclusion.